The priestly sins a novel - Greeley, Andrew M., 1928- (New York : Forge, 2004)
Father Herman Hoffman, a gifted and innocent young priest, during his first parish appointment, witnesses child abuse in the parish rectory. When he reports the abuse, he is rebuffed by the archbishop and learns the harsh fate of the whistleblower in the Catholic Church.
Keywords: Clergy -- Fiction; Catholics -- Fiction; Whistle blowing -- Fiction; Child sexual abuse by clergy -- Fiction; Psychological fiction; Christian fiction